Molluscum contagiosum within an epidermal cyst. - Ingravallo, G. (European Journal of Pediatric Dermatology, 2022)
Molluscum contagiosum is a skin infection caused by a double-stranded DNA pox virus. It mainly affects children, in whom it represents the most frequent viral infection of the skin. A peak of incidence occurs at 2-3 years of age. Before one year of age, it is generally not observed due to an immune protection transmitted by the mother (5). This data together with the spontaneous regression and the rare presence in adults speak in favor of silent infections that confer immunity to the majority of the population. (...)